The COVID-19 Reader 2020
DOI: 10.4324/9781003141402-20
|View full text |Cite
|
Sign up to set email alerts
|

Strong Social Distancing Measures in the United States Reduced the COVID-19 Growth Rate

Abstract: State and local governments imposed social distancing measures in March and April of 2020 to contain the spread of novel coronavirus disease 2019 (COVID-19). These included large event bans, school closures, closures of entertainment venues, gyms, bars, and restaurant dining areas, and shelter-in-place orders (SIPOs). We evaluated the impact of these measures on the growth rate of confirmed COVID-19 cases across US counties between March 1, 2020 and April 27, 2020. An event-study design allowed each policy's i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
148
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(155 citation statements)
references
References 13 publications
4
148
0
3
Order By: Relevance
“…Most previous observational analyses of NPIs – primarily stay-at-home and social distancing directive – have focused on cases rather than fatalities, either in individual countries 24-27 or across multiple countries 28-29 . There is limited existing work regarding the effect specifically of stay-at-home policies on deaths, in Brazil 11 , France 12-13 , and the United States 14-15 , but not of the full range of government interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Most previous observational analyses of NPIs – primarily stay-at-home and social distancing directive – have focused on cases rather than fatalities, either in individual countries 24-27 or across multiple countries 28-29 . There is limited existing work regarding the effect specifically of stay-at-home policies on deaths, in Brazil 11 , France 12-13 , and the United States 14-15 , but not of the full range of government interventions.…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, a variety of policies were implemented at the state level or the county level including shelter‐in‐place orders (SIPOs),10 closures of restaurants/bars/entertainment‐related businesses, bans on large events, and closures of public schools. The effectiveness of these policies varied widely; SIPOs and closures of nonessential businesses worked toward curtailing COVID‐19 while the prohibition of large events and closure of public schools did not show signs of slowing down COVID‐19 (C. Courtemanche et al, 2020; C. J. Courtemanche et al, 2020; Dave et al, 2020, 2021). Statewide SIPOs had the strongest effect, accounting for a 37% decrease in confirmed cases 15 days after implementation (Abouk & Heydari, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Given the focus of our current study, we restrict our review to studies that explore COVID-19 transmission and mortality rate at an aggregated spatial scale. To elaborate, these studies explored COVID-19 transmission and mortality rates at the national 46 , regional 7 , state 8 , county 914 , city 15 and zip code levels 16 . A majority of these studies considered transmission rate as the response variable (transmission rate per capita).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding health indicators, earlier research found that smokers, obese and individuals with existing health conditions are more likely to be severely affected by COVID-19 11 . In terms of mobility trends, studies showed that staying at home and effective mobility restriction measures significantly lower the COVID-19 transmission rate 4,7,9,10,14 while increased mobility resulted in increased COVID-19 transmission 12,19 . Finally, among health care infrastructure attributes, testing rate is linked with reduced risk of COVID-19 transmission 4,5 .…”
Section: Introductionmentioning
confidence: 99%